The mysterious Mr. Quin - Christie, Agatha (b, 2003)
A mysterious stranger appears at a New Year's Eve party, becoming the enigmatic sleuthing sidekick to the snobbish Mr Satterthwaite...
Keywords: English fiction; Detective and mystery stories, English